2012
DOI: 10.3390/ijerph9113843
|View full text |Cite
|
Sign up to set email alerts
|

Examining Land-Use/Land-Cover Change in the Lake Dianchi Watershed of the Yunnan-Guizhou Plateau of Southwest China with Remote Sensing and GIS Techniques: 1974–2008

Abstract: Monitoring land-use/land-cover change (LULCC) and exploring its mechanisms are important processes in the environmental management of a lake watershed. The purpose of this study was to examine the spatiotemporal pattern of LULCC by using multi landscape metrics in the Lake Dianchi watershed, which is located in the Yunnan-Guizhou Plateau of Southwest China. Landsat images from the years 1974, 1988, 1998, and 2008 were analyzed using geographical information system (GIS) techniques. The results reveal that land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…Lake Dianchi (24 • 51 N, 102 • 42 E) lies in the center of the watershed, with an area of 309.5 km 2 and a storage capacity of 1.56 billion m 3 (at a water level of 1887.4 m). As the largest lake on the Yunnan-Guizhou Plateau and the sixth-largest freshwater lake in China, Lake Dianchi has been given the name of "Pearl of the Plateau" concerning its significant functions for water supply, flood regulation, fisheries and biodiversity conservation Zhao et al, 2012). Although the Lake Dianchi basin area makes up only 13.9 % of Kunming, it contributed 75.5 % of the city's gross domestic product, acting as the most active economic area in Yunnan Province (Pan and Gao, 2010).…”
Section: Characterization Of the Lake Dianchi Basinmentioning
confidence: 99%
“…Lake Dianchi (24 • 51 N, 102 • 42 E) lies in the center of the watershed, with an area of 309.5 km 2 and a storage capacity of 1.56 billion m 3 (at a water level of 1887.4 m). As the largest lake on the Yunnan-Guizhou Plateau and the sixth-largest freshwater lake in China, Lake Dianchi has been given the name of "Pearl of the Plateau" concerning its significant functions for water supply, flood regulation, fisheries and biodiversity conservation Zhao et al, 2012). Although the Lake Dianchi basin area makes up only 13.9 % of Kunming, it contributed 75.5 % of the city's gross domestic product, acting as the most active economic area in Yunnan Province (Pan and Gao, 2010).…”
Section: Characterization Of the Lake Dianchi Basinmentioning
confidence: 99%
“…Analyzing and interpreting such data over time plays a critical role in monitoring changes, and facilitates identification of driving forces that bring changes in the landscape [20]. Several studies have integrated landscape metrics with LULC classifications derived from remote sensing images to quantify the patterns of a landscape and relate to the processes driving the changes [4,20,23]. For example, Wang and Wang [4] used LULC data derived from remote sensing images, in combination with landscape metrics, to evaluate changes in the landscape of Yanqi Basin, China.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of studies on the effects of LULC changes on the spatial patterns of the landscape and water quality of lake basins [4,23,35]. Thus, some studies suggested the study of LULC changes as a critical step that should be considered in the environmental protection strategy and sustainable resource management of lake basins.…”
Section: Introductionmentioning
confidence: 99%
“…This technology can provide information on both biological (vegetation and its dynamics) and physical conditions (variations in terrain and morphological features) of LULCC. However, standard LULCC information generated from remote sensing data over the decades continues to be a challenging task, owing to the prevailing variations in spatial resolution of satellite data [10][11][12]. Numerous recent and on-going studies have improved both the measurements and understanding of factors influencing LULCC at the global scale, which in turn have paved the way to assimilate them in climate models [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%